Maximum streamflow: brief description of concepts and methods of regionalization - Barbosa, Mariana Abibi Guimarães Araujo; Anjinho, Phelipe da Silva; Santos, Allita Rezende dos; Okawa, Cristhiane Michiko Passos; Mauad, Frederico Fabio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
One of the main problems in the development of hydrological studies is the scarcity of measured data. In Brazil, because of its great water availability, and due to its territorial extension, the costs of implementing and maintaining hydrometric stations is a challenge, compromising hydrological monitoring and data collection. Therefore, developing methods that contribute to the estimation and transfer of information is essential for better integrated management of water resources, highlighting the importance of maximum streamflow data on issues such as flood mitigation. In order to solve this problem, streamflow regionalization models appear as tools to estimate hydrological data in ungauged sites, that is, it allows the transfer of measured or simulated information between homogeneous basins. In view of this, this article has the objective of investigate and describe the main methodologies developed and disseminated in the literature on hydrological regionalization, especially in relation to maximum streamflow, by means of a brief literature review. In short, it can be observed that different methods are applied and tested in order to obtain regionalization results associated with lower uncertainties, and there is no standardized method, once there are hydrological specificities of different locations.